Enhancing the quality of life by maintaining the vernacular features of the functional spaces of Malay kampong houses - GhaffarianHoseini, AmirHosein; Ibrahim, Rahinah; Baharuddin, Mohd Nasir (2009)
Contemporarily, the quality of residential functional spaces has been mostly based on style and modernity rather than the tradition of that particular regional context. With the rapid modernization of Malaysia, the kampong house as the Malay vernacular architecture has been replaced by modern architecture. Moreover, the consideration of vernacular architectural factors during the modern design process has been decreased. Accordingly, various aspects of kampong house which identified it as a major vernacular value, has been lost inside contemporary functional spaces. Therefore, the neglected fundamental features of functional spaces during the design process would be the vernacular architectural features. In this research, archival search method will be conducted to study the vernacular architectural features of Malay vernacular houses. These features contain the spatial characteristics of functions and spaces based on local needs which will influence the quality of functional spaces. The study is limited to all vernacular architectural features of Malaysia which can be utilized for contemporary residential functional spaces during the design process. This research will lead to the identification of vernacular architectural features which could be influential in enhancing the quality of functional spaces. Correspondingly, functional spaces will be intertwined with vernacular functional spatial features and cultural values which will address the local needs in terms of vernacular features.